2015
DOI: 10.1158/0008-5472.can-15-0840
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 Mutation Induces Reprogramming of Pyruvate Metabolism

Abstract: Mutant isocitrate dehydrogenase 1 (IDH1) catalyzes the production of 2-hydroxyglutarate but also elicits additional metabolic changes. Levels of both glutamate and pyruvate dehydrogenase (PDH) activity have been shown to be affected in U87 glioblastoma cells or normal human astrocyte (NHA) cells expressing mutant IDH1, as compared to cells expressing wild-type IDH1. In this study, we show how these phenomena are linked through the effects of IDH1 mutation, which also reprograms pyruvate metabolism. Reduced PDH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
148
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(159 citation statements)
references
References 53 publications
10
148
0
1
Order By: Relevance
“…In a recently published study (6), we confirmed that a significant reduction in PDH activity occurs in both our U87 and NHA mutant IDH1 cells compared to wild-type (6). 13 C MRS probing the fate of 1- 13 C-glucose to 4- 13 C-glutamate, and hyperpolarized 13 C MRS probing the fate of 2- 13 C-pyruvate to 5- 13 C-glutamate, showed that reduced PDH activity also resulted in a reduction in glucose flux to glutamate in IDH1 mutant cells relative to wild-type.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…In a recently published study (6), we confirmed that a significant reduction in PDH activity occurs in both our U87 and NHA mutant IDH1 cells compared to wild-type (6). 13 C MRS probing the fate of 1- 13 C-glucose to 4- 13 C-glutamate, and hyperpolarized 13 C MRS probing the fate of 2- 13 C-pyruvate to 5- 13 C-glutamate, showed that reduced PDH activity also resulted in a reduction in glucose flux to glutamate in IDH1 mutant cells relative to wild-type.…”
supporting
confidence: 89%
“…In summary, our recent study (6) identifies a potential therapeutic target for mutant IDH1 low-grade gliomas, as well as an associated companion MRS biomarker for agents that would modulate that target.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a common feature, however, mutant IDH1 drives widespread metabolic alterations in cancer cells(17). These include the production of 2-hydroxyglutarate (2HG)(18), modulation of HIF1α(19), pyruvate dehydrogenase(20), and lactate dehydrogenase(21), as well as altered citric acid cycle flux(22), and depleted steady-state pools of several canonical metabolites including glutathione(23) and nicotinamide adenine dinucleotide (NAD+)(24). This altered baseline metabolism results in the exposure of distinct enzymatic targets, including glutaminase(25) and the NAD+ biosynthetic enzyme nicotinamide phosphoribosyltransferase (NAMPT)(24), to selective inhibition with small molecules, resulting in genotype-specific metabolic vulnerabilities in IDH mutant cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Of recent interest is the use of labeled glucose to study the role of mutant isocitrate dehydrogenase on aggressive cancer phenotypes. 28 Since muscle tissue relies heavily on -oxidation for energy, labeled short, medium, and long chain fatty acids have been used to study metabolism under a range of conditions that include normal, ischemic, and diabetic perfused hearts. 29,30 The focus in liver perfusion has been somewhat different.…”
Section: Mrsmentioning
confidence: 99%